When knowledge fades but loyalty persists: examining the contextual dynamics of media effects on vaccination intentions in China - Zhang, Ruifen; Jia, Hepeng; Wu, Fuzhong; Chen, Anfan; Luo, Xi (Frontiers in Communication, 2025)
IntroductionMedia exposure shapes health behaviors directly and via cognitive and affective/attitudinal mediators. However, how different types of mediating route’s function and how evolving environments affect these mediators remains understudied.MethodsDrawing on three national survey waves fielded at distinct stages of China’s COVID-19 response (April 2021 vaccine rollout; April 2022 zero-COVID debate; January 2023 post-lockdown), this study compares the mediating roles of biomedical knowledge, perceived risk, trust in scientists, and nationalism in linking media use to vaccination intentions.ResultsAcross phases, affective/ attitudinal pathways—especially nationalism, and trust in scientists except—were the most stable and consequential mediators. By contrast, cognitive pathways were weaker and context-dependent. These shifts track changes in vaccine novelty, policy coherence, and the intensity of state mobilization, suggesting that strong mobilization and conflicting expert cues can dampen cognitively demanding routes while amplifying identity- and authority-based heuristics.DiscussionThe findings underscore that evolving sociopolitical contexts reshape how media influence health behaviors and point to culturally informed, context-sensitive strategies that balance appeals to collective identity with clear, credible information.